LIE ALGEBRA REPRESENTATIONS AND RIGGED HILBERT SPACES: THE SO(2) CASE - Enrico Celeghini; Manuel Gadella; Mariano A del Olmo (Acta Polytechnica, 2017)
It is well known that related with the irreducible representations of the Lie group SO(2) we find a discrete basis as well a continuous one. In this paper we revisited this situation under the light of  Rigged Hilbert spaces, which are the suitable framework to deal  with both discrete and bases in the same context and in  relation with physical applications.